Gender Violence in the Family: Penal Juridical Perspective - Nares Hernandez, Jose Julio; Martínez García, Dulce Gloria; Colín García, Ricardo (CIENCIA ergo-sum; Vol. 22 Núm. 2 (2015): CIENCIA ergo-sum (julio-octubre 2015), 2015)
In the present work, the Federal Constitution and international treaties that oblige the State criminally to guarantee the women’s human rights to have a life free of violence at home, from a protectionist perspective are analyzed. It is concluded that to fulfill with such obligation, the legislative creation of a penal norm to punish the domestic violence associated with gender based violence is unavoidable. This legislative action would be part of a new criminological policy specifically dedicated to the prevention, punishment and eradication of gender based violence at home